Pengaruh Persepsi Kegunaan, Kemudahan Penggunaan dan Risiko Terhadap Minat Mahasiswa Menggunakan Sistem Blockchain - Dita Witami, Dewa Ayu; Suartana, I Wayan (E-Jurnal Akuntansi; Vol 28 No 2 (2019)DO - 10.24843/EJA.2019.v28.i02.p21, 2019)
The purpose of this study was to determine the effect of perceived usefulness, perceived ease of use and risk perception of interest in using the blockchain system in financial technology. The population of this study was undergraduate students majoring in accounting FEB Udayana University class of 2015-2018. Methods Determination of samples in this study using saturated sampling techniques. The sample in this study amounted to 294 people. The data collection method used is the survey method with a questionnaire. The data analysis technique used is multiple linear regression analysis. Based on the results of the analysis it was found that perceived usefulness and perceived ease of use had a positive effect on the interest in using the blockchain system in financial technology. But the perception of risk has a negative effect on interest in using the blockchain system in financial technology. Keywords: Perception of usability, perception of ease of use, perception of risk and interest in using the blockchain system.